About the acceleration rate of relativistic beams by a surface wave in a dielectric laser accelerator - Bolshov, O.O.; Vasiliev, A.V.; Povrozin, A.I.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2021)
An analysis of the dependence of the acceleration rate of charged particles by a surface wave arising when a laser pulse/(plane wave) is incident on the interface between two dielectric media on the phase velocity of the excited wave is carried out. It is shown that at resonance acceleration this dependence has a maximum, for ultra-relativistic particles the acceleration rate tends to zero. The dependences of the acceleration rate on the phase velocity of the excited wave for various refractive indices (dielectric permittivities) of optically transparent medias are investigated analytically and numerically.